PERESEPAN BERPOTENSI TIDAK TEPAT, LUARAN KLINIS DAN EFEK SAMPING OBAT PADA PASIEN GERIATRI DENGAN TERAPI ANTIHIPERTENSI - Muh. Irham Bakhtiar; Dinny Seppraudiva (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Hypertension in geriatric patients poses a clinical challenge due to age-related physiological changes that increase the risk of Potentially Inappropriate Medications (PIM), adverse drug events (ADE), and difficulty in achieving target blood pressure. This study aimed to evaluate potentially inappropriate antihypertensive prescribing using the Indonesian version of the STOPP criteria, assess blood pressure target achievement based on three guidelines (NICE 2019, JNC 8, and ACC/AHA 2017), and identify ADEs assessed using the Naranjo algorithm. This was a descriptive observational study with a prospective approach conducted through medical record review and interviews with hospitalized geriatric patients at Hospital X in Samarinda. The results showed a 23.08% prevalence of PIM, including the use of furosemide without clear indication, clonidine as an antihypertensive, and high-risk diuretic combinations. Failure to achieve blood pressure targets was found in 35.71% (NICE 2019), 28.57% (JNC 8, 2014), and 78.57% (ACC/AHA, 2017), indicating that stricter targets are more difficult to achieve in older adults. There were three ADE cases (21.43%), consisting of two cases of renal dysfunction associated with candesartan and one case of abdominal pain due to furosemide. Causality was assessed using the Naranjo algorithm and validated by clinical pharmacists using the 30th edition of the Drug Information Handbook (2021). This study highlights the importance of individualized antihypertensive therapy evaluation in elderly patients to prevent PIM, improve clinical outcomes, and reduce adverse events. Active involvement of clinical pharmacists and data-driven clinical decision support systems are essential to enhance medication safety and therapeutic effectiveness in the geriatric population.